The Concept-Strategy of Ecosystem Management through Tax Mechanisms of Financial Security - SHOKHNEKH, Anna Vladimirovna; SKITER, Natalia Nikolaevna; ROGACHEV, Alexey Fruminovich; PLESCHENKO, Tatyana Vitalyevna; MELIKHOVA, Elena Valentinovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The standard of well being of the ecosystem (environment) determines possible approaches for sustainable development of the economy of the studied subject. Today, the environmental safety involves large-scale, long-term and expensive programs. The basic concept-strategies of ecosystem management through tax mechanisms of financial security are considered in this article; the goal, objectives, subjects, objects, and subject matters of tax mechanisms of the system are also highlighted taking into account the intersectoral externalities in the financial security system.